5G value plane, the next generation of BSS/OSS consolidated architecture - Jie SUN; Tao SUN; Zhenqiang SUN; Yunxin LIU; Aidong YANG; Da WANG; Peng WANG; Xiaozhou YE; Ye OUYANG (Dianxin kexue)
With the development of the mobile communication and Internet technology, the traditional communication business has been developed from voice communication services to diversified and personalized information services, and the value chain structure of the communication industry has been changed from the mobile network operator (MNO)-centered mode to the user experience-centered mode.With the concept of “content-driven”, Internet content providers update their products actively to satisfy the users’ needs, which results in a rapid increase in the market share, while the MNOs are gradually being “pipelined” in the industry value chain.In the process of the digital transformation, MNOs have achieved the on-demand scheduling, flexible adaptation, and rapid deployment by reconfiguring and abstracting 5G network functions, and have enhanced the user experience using a user centric operation model based on the business support system (BSS)/operation support system(OSS)(BO) consolidation to ultimately achieve the enhancement in the value chain.On the basis of reviewing the development of the communication industry’s value chain, the challenges for MNOs to promote their values were analyzed.Meanwhile, a 5G value plane architecture based on embedded services in 5G networks was proposed, and the typical application scenarios were given.Path suggestions for the evolution of the 5G value plane were provided, which help MNOs to build the next generation of BSS/ OSS consolidation.